Building Information Modelling: Perceived value and opportunities An investigation of real estate owners and appraisal firms - ALMQUIST, PER; GUSTAFSSON, NIKLAS (My University, 2018)
The real estate sector is under digitalization where traditional replacements of paper to digital equivalents are heading towards more intelligent and interoperable solutions. Building Information Modelling, also known as BIM, has developed as a tool to be used in the industry, having seen the benefits in construction and architecture. The advantages with BIM have been research to a higher extent within these branches and the possibilities for development in the real estate sector should be examined further. The cost of operating and managing a building could be many times higher than the actual construction, which gives a reason to focus more on facilities management. The report is embracing a qualitative method and has been developed from six semistructured interviews from actors who are located in the city of Gothenburg. A literature review has been conducted in order to create a theoretical framework, which later on has been analysed together with the empirical material. The report investigates if there are any incentives for the property owners in Gothenburg to implement BIM. To analyse BIM´s possibilities in operations and compare it with how property owners work today. To examine if BIM can affect the real estate value in a positive manner, which was the report main research question, could it increase the interest in implementing BIM. Furthermore, there has mainly been two professions in focus in this report, property owners and appraisers. This thesis could not support that a property would be valued higher by having BIM implemented. Other economic factors could neither be found, however there is a potential for BIM in the real estate sector since the model could be used to save time and costs. This can be made due to the rich information base that BIM can entail and thereby have a large amount of information available. The information must be relevant to several professions in an organization to benefit to whole company. BIM could also be used in visualisation of buildings without having to visit the actual site and also for refurbishments.
Keywords: Samhällsbyggnadsteknik; Civil Engineering